Character Development Training and Education for Public Officials: Examining Implementation and Ethical Leadership Outcomes - Agus Ramdani; Sujarwo Sujarwo; Yudan Hermawan; Gumpanat Boriboon; Sri Nurhayati (IJECA (International Journal of Education and Curriculum Application), 2025)
Ethical leadership remains a critical concern in Indonesia’s public sector, where bureaucratic integrity is often undermined by systemic challenges. This study aims to examine the implementation and outcomes of character development training in fostering ethical behavior among public officials. The research was conducted at BP3KSDMT, a specialized training institution under the Ministry of Transportation, using a qualitative case study approach. Data were collected from 10 respondents—including facilitators, administrators, and training participants—through semi-structured interviews, participant observations, and document analysis. Triangulation and member-checking were employed to ensure data validity and reliability. Thematic analysis was conducted manually to identify key themes and recurring patterns related to training implementation and results. The findings reveal that experiential learning methods—such as role-playing, team-building exercises, and scenario-based simulations—positively influenced training outcomes, particularly in ethical decision-making, personal accountability, and teamwork. Post-training evaluations reported a 25% increase in ethical decision-making proficiency, a 34% improvement in awareness of bureaucratic ethics, and a 29% enhancement in collaborative problem-solving skills. These outcomes underscore the program’s effectiveness in achieving meaningful training results within the Indonesian civil service. This study contributes empirical evidence to the limited body of research on ethics training in Southeast Asian bureaucracies. In contrast to prior studies centered on Western models or conceptual frameworks, it offers context-specific insights into the practical value of character development. The findings highlight the importance of sustained investment in training implementation and call for further research on the long-term impact of such initiatives on institutional culture and accountability.